(untitled) (Journal of the College of Education for Women, 2019)
The research is a contemporary stylistic study of the text that expresses the psychologicalmeanings in Nahj Al-Balaghah.The research is divided to three chapters.The first chapter : characteristics of psychological text.It is about the power to influence the addressee ,that is to say ,the text influence powerconnects with vulnerability and emotions inside the addressee spirit and his response toviolent effects shaking his feelings and that is represented in outbreaking of words vitality andhomogeneously. The Imam’s wrath , grief , love to rightness , hatred of falsehood anddeviation from Islam arouses the words and emotions through :1. Reduction in words and expansion in meaning by means of inspiration of the intentionalmeaning.2. Consistency and coherence: illustrates the connection between words and forms ofconsistency.3. Homogeneity between the components of the sentence to illustrate the closeness andattachment of words by formatives and grammatical links.4. Script overlap between The Holy Quran and Nahj Al-Balaghah in those texts.The second chapter : coherence in The Holy Quran text whether among It’s words or phrases .The most important links are : conjunctions , conductive names , linking by meaning change ,linking by pronouns , linking by demonstrative pronouns and linking by repetition.The third chapter : structural phenomena in psychological text which consist : elaboration anddetailing in meaning or structural expansion of the the sentences , repetition , sequence ,diversification in syntax composition , conformity and violation. All these phenomena arecommon in the texts of Nahj Al-Balaghah.